Antagonistically Functionalized Diatom Biosilica for Bio‐Triboelectric Generators. Issue 20 (15th April 2022) - Rajabi‐Abhari, Araz; Lee, Jeehee; Tabassian, Rassoul; Kim, Jong‐Nam; Lee, Haeshin; Oh, Il‐Kwon
Abstract: Although biomaterial‐based triboelectric nanogenerators (Bio‐TENGs) for use in wearable electronics and implantable sensors have been developed, power generation is not suitable for satisfying the basic requirements for practical applications. Here, to greatly enhance output performances of Bio‐TENG devices, an antagonistic approach of diatom frustules (DFs) with amine and fluorine chemical functionalizations is reported. The DFs are treated with piranha solution to increase the density of hydroxyl groups and tribo‐positive and tribo‐negative composite films are designed with antagonistically functionalized DFs. The tribo‐positive composites having electron donating functionality consist of aminated DFs and cellulose nanocrystals (CNCs), while the tribo‐negative composite is composed of fluorinated DFs and polydimethylsiloxane (PDMS). An antagonistically and chemically functionalized TENG (ACF TENG) with an efficient contact area of 9.6 cm 2 under a force of 8 N and a frequency of 5 Hz exhibits an output voltage of 248 V, a short‐circuit current of 16.4 µA, and a power density of 2.01 W m −2, which is 16.6 times higher than a reference (CNC:PDMS) TENG. This study shows a simple antagonistic approach for chemical functionalization as an efficient method to manipulate the tribo‐polarity of bio‐additives for enhancing power generation of Bio‐TENGs. Abstract : Antagonistically functionalized diatom biosilica can be used as efficient additives in tuning output performances of biomaterial‐based triboelectric nanogenerators devices, by taking advantage of the synergy among particle loading, chemical functionalization, and physical surface roughening.